Cane Water Content and Yield Responses of Vitis vinifera L. cv. Sultanina to Overhead Irrigation During the Dormant Period - Myburgh, P.A.; van der Walt, L.D. (South African Journal of Enology and Viticulture, 2017)
The possibility to increase grapevine cane water content during the dormant period by applying overhead irrigation, and thereby increasing yield, was investigated in a semi-arid summer rainfall climate. A field trial was carried out with Sultanina grapevines in the Lower Orange River region over two seasons. During the 2000/2001 season control grapevines (Tl) that received no overhead irrigation in winter were compared to ones receiving overhead irrigation applied over a ca. 30-day period, starting either in July (T2), mid-July (T3), August (T4) or mid-August (TS).  Overhead irrigation was applied as ten-minute pulses on the hour from 10:00 until 16:00. Due to the lack of winter rainfall, all treatments received normal, under-vine irrigation in winter to avoid severe water deficits. All treatments, except T2, were repeated during the 2001/2002 season. Two additional treatments which received no irrigation during winter were included during the second season. Of these two, T6 received overhead irrigation in August, whereas T7 received no overhead irrigation. Compared to the Tl control, overhead irrigation applied during August 2000 (T4) not only increased cane water content measured before bud break, i.e. early September, but also increased yield.  The other overhead irrigation treatments did not affect cane water content or yield. During the second season overhead irrigation started in mid-July (T3) or in the beginning of August (T4) induced higher yields compared to grapevines that received overhead irrigation in the period before bud break (TS). Where available soil water depletion of 90% occurred, overhead irrigation (T6) seemed to negate the adverse effects of dry soil on yield. In contrast, cane water content and yield were considerably lower where neither normal nor overhead irrigation was applied (T7), compared to T3 and T4. These results confirmed that overhead irrigation can increase cane water content and yield, and that soil water deficits during the dormant period should be avoided. Overhead irrigation and/or water deficits during winter did not affect cane mass, as measured at the end of the following growing season.